Pathogenic identification and antibiotic susceptibility of the microorganisms isolated from urine samples of UTI patients - Miah, Md Ibrahim; Ahmed, Tasnia; Munshi, Saurab Kishore (Stamford Journal of Microbiology, 2017)
Urinary tract infection (UTI) is the infection that occurs in the urinary tract by the invasion of pathogenic bacteria, fungi, virus etc. under some circumstances only. Some common pathogenic bacteria associated with UTI include Escherichia coli, Proteus spp., Streptococcus spp., Staphylococcus spp., Pseudomonas spp. In the ongoing research work, about 30 UTI patients were selected randomly to detect the pathogen responsible for causing urinary tract infection and also to demonstrate their drug resistant traits. Among the 30 samples, about 14 samples were found to harbor Proteus spp. (1×104 cfu/ml to 1×105 cfu/ml). Escherichia coli was found to be the second predominant agent for UTI and recovered from 13 samples. Among the rest 3 samples, Pseudomonas spp. was found in 2 samples and Klebsiella spp. was found in one sample. Identified isolates showed resistance against different ranges of antibiotics. The study findings revealed the fact that emerging drug resistance of different pathogenic bacteria could become the major difficulties in the treatment of infectious diseases like UTI. Stamford Journal of Microbiology, Vol.6(1) 2016: 34-38